An evaluation of the employment effects of barriers to outsourcing - Subhayu Bandyopadhyay; Sugata Marjit; Lei Yang (Institute for the Study of Labor (IZA), 2011)
Barriers to outsourcing that are being currently implemented in the US effectively tax its companies who export jobs through outsourcing. The objective is to raise domestic employment. Given that many of the important international markets where the US has a comparative advantage feature non-atomistic firms, we evaluate the implications of such policies in an oligopolistic context. We find that while an outsourcing tax favors domestic workers by causing firms to switch to a greater use of domestic sources (the substitution effect), the loss in international competitiveness has a negative volume effect (the output effect), which pulls in the other direction. First, we identify the conditions that determine the relative strengths of these effects, which inform us about the conditions under which such a tax achieves its stated objective. Next, we consider the international policy interdependence that arises when a competing nation also engages in such a policy. An interesting finding is that even if a unilateral tax by the US raises its employment, this may turn around in a Nash policy equilibrium, where the competing nation abandons free trade and also engages in unilateral outsourcing policies. Finally, we extend the basic model to look at the effects of credit shortage and product differentiation. Interesting findings are that both a credit crisis (as in recent years) and increased product differentiation tend to worsen the employment effects of the outsourcing tax. The qualitative nature of our findings is similar between Cournot and Bertrand competition, suggesting that our results are robust to the mode of strategic behavior.
urn:nbn:de:101:1-201104084375
Keywords: F13; 330; outsourcing tax; employment effects; oligopolistic competition; product differentiation; Outsourcing; Offshoring; Steuer; Steuerwirkung; Beschäftigungseffekt; Oligopol; Internationaler Wettbewerb; Produktdifferenzierung; Theorie; USA